2019
DOI: 10.3892/etm.2019.8324
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin a attenuates hyperlipidemic pancreatitis in rats via the PPAR‑γ/NF‑κB signaling pathway

Abstract: The therapeutic effect of saikosaponin a (SSa) on hyperlipidemic pancreatitis (HP) is not completely understood. The aim of the present study was to investigate the therapeutic effect and the underlying mechanism of SSa using a rat model of HP. Following successful establishment of the HP rat model, different doses of SSa (low dose group, 10 mg/kg or high dose group, 20 mg/kg) were administrated. Histopathological examination, the wet/dry (W/D) ratio and myeloperoxidase (MPO) activity of the pancreatic tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Accordingly, recent research seems to have granted special interest for the search of effective natural glucosidase and lipase inhibitors (Hamden et al, 2017). Previous research studies have shown that medicinal plants exhibited pronounced inhibitory effects towards the activities of a-amylase, lipase and inflammation (Kang et al, 2015;Ghasemian et al, 2016;Von Dentz, et al, 2020;Joshi et al, 2018;Feng et al, 2020;Mohamed et al, 2020;Tiss et al, 2020). In fact, Plants are a source of bioactive secondary metabolites such as glycosides, saponins, flavonoids, steroids, tannins, alkaloids and terpenes, which act as strong antioxidant to protect body from oxidative damage (Upreti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, recent research seems to have granted special interest for the search of effective natural glucosidase and lipase inhibitors (Hamden et al, 2017). Previous research studies have shown that medicinal plants exhibited pronounced inhibitory effects towards the activities of a-amylase, lipase and inflammation (Kang et al, 2015;Ghasemian et al, 2016;Von Dentz, et al, 2020;Joshi et al, 2018;Feng et al, 2020;Mohamed et al, 2020;Tiss et al, 2020). In fact, Plants are a source of bioactive secondary metabolites such as glycosides, saponins, flavonoids, steroids, tannins, alkaloids and terpenes, which act as strong antioxidant to protect body from oxidative damage (Upreti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The peroxisome proliferators-activated receptor γ(PPARγ) is mainly expressed in liver and adipose tissues and it plays a role in promoting the differentiation and maturation of adipocytes and regulating the activation of signaling pathways responsible for lipid metabolism and the expression of related genes [21]. It is believed that hyperlipidemia can exacerbate the in ammatory response and pathological injury of AP, the mechanisms of which may be related to the down regulation of PPARγ mRNA expression [ 22,23]. For this reason, treatment with PPARγ agonist can relieve the in ammatory response of pancreatic tissues in HLAP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it significantly decreased the levels of pancreatic enzymes (MPO, amylase and lipase) and reduced proinflammatory cytokines (TNF‑α, IL-1β and IL-6) release by suppressing the NF-κB signalling pathway and promoting the expression of peroxisome proliferator-activated receptor-γ (PPAR-γ) (Feng et al. 2019 ). Taken together, SSa exerted therapeutic effects on hyperlipidaemic pancreatitis.…”
Section: The Potential Mechanisms Of Phytochemicals In the Attenuatio...mentioning
confidence: 99%